A tapestry Women from The vicissitudes of history, place and daily life /Richard Chase Smith - Chase Smith Richard (Perú : OXFAM, 2000)
Trata de a tapestry Women from The vicissitudes of history, place and daily life.
1.Cuaro claves para entender la complrjidad en el mundo indígena 2.Reexaminando el Tapiz indijena:Temas y desafios para el nuevo milenio 3.The warp:Territory and economy
incluye índice
Col Educ
Keywords: 1.LA TRAMPA:IDENTIDAD Y GOBERNABILIDAD 2.MOVING INTO THE NWE MILLENIUM 3.VOMMONALTIES IN A WORLD OF DIFFERENCE